Lexicografía implícita en textos del Padre Jesuita Fernão Cardim - Gonçalves, Maria Filomena (2013)
This study analizes a specific textt - Tratados da Terra e Gente do Brasil - by the Father Fernão Cardim (1540/1548-16259, a Jesuit missionary in Brazil - aiming at describing both the typology of definition and the linguistic processes which Cardim's texto closer to lexicography.